PERSEPSI SISWA TERHADAP PELAKSANAAN LAYANAN BIMBINGAN KELOMPOK DI SMA NEGERI 1 MUARO JAMBI - Rts. Ainun (Jurnal Ilmiah Dikdaya, 2018)
Abstract: Student’s perception of implementations of group guidance service which consist of planning, implementing, evaluating and follow up action is one related entity that must be implemented optimally in conseling guidance program. The purpose of group guidance service are to help individuals attaining some information and to take decision based on the student’s insight and experience in daily life. The aim of this research is to know student’s perception of group guidance service in SMA Negeri 1 Muaro Jambi. This study uses a survey method. The data collection of this study is a questionnaire which refers to the criteria of group guidance. This study involves 40 students as the purposive sampling. The result show that students perception of group guidance service in class XI IPS SMA Negeri 1 Muaro Jambi is categorized in a good term. The average score is around 78,47%. For each indicator, it consists of 85,63% for planning group guidance service, 72,75% for implementing group guidance service, 75,50% for evaluating group guidance service, and 80% for follow up action.Keywords: Perceptions, Group Guidance Service